Pengaruh Customer Satisfaction Terhadap Brand Loyalty dengan Brand Trust Sebagai Variabel Mediasi pada Produk Elektronik TV LED Merek LG di Kota Surakarta - Dimas Aji Pramana; Wafiatun Mukharomah (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2023)
This study aims to analyze the effect of customer satisfaction on brand loyalty mediated by brand trust on LG brand LED TV products in Surakarta City. This research is included in quantitative research. The population in this study are customers of LG brand tv products who live in the city of Surakarta. The sample used in this study was 122 respondents. The sampling technique used was non-probability sampling and the approach used in determining the sample was purposive sampling. Sources of data used in this study using primary data. Methods of data collection using a questionnaire. Data analysis using Smart PLS application. The results of the analysis in this study show (1) customer satisfaction towards brand loyalty is positive and insignificant (2) customer satisfaction towards brand trust is significant positive (3) brand trust to brand loyalty is significant positive (4) brand trust fully mediates the influence of customer satisfaction on brand loyalty and the results are significant positive.